Теорії ефективної школи та удосконалення школи: аналіз концептуальних засад освітніх змін у розвинених англомовних країнах - Шихненко, Катерина (Studies in Comparative Education, 2013)
У статті розглянуто особливості розвитку теорій ефективної школи та удосконалення школи як складових теорії освітніх змін, що склалася у англомовній педагогічній думці у кінці ХХ ст. – на початку ХХІ ст. В статье анализируются особенности формирования и развития теорий эффективной школы и усовершенствования школы как составляющих теории образовательных изменений, которая сформировалась в педагогике США, Канады и Великобритании в конце ХХ ст. – начале ХХI ст. The article analyzes the peculiarities of the formation and development of the school effectiveness theory and school improvement theory as components of the educational change theory which occurred in the modern pedagogy of the USA, Canada, and Great Britain. The existence of the school effectiveness theory and school improvement theory as independent scientific areas at the initial stage and lack of synergy between them are emphasized. 80–90 years of the twentieth century as key ones that intensified the problem of effective school as an organization, as well as its ability to update and improve own efficiency are determined. The concept of an effective school as an institution focused on the best students’ academic results in a maximum number of cognitive and other areas is defined. Eleven features of effectively working schools and their fundamental characteristics are described. The factors that limit the productive activities of schools or lead to their crisis are analyzed. Key things that contribute to the removal of school crisis are specified. The article also highlights the changes of scholars’ interests from effective school characteristics to the issues of school development and improvement in the 80s years of the twentieth century, and school improvement theory formation that identified the strategies of educational changes at the end of the twentieth century – beginning of the twenty first century. It is determined that school improvement approach supports educational transformations that focus on skills, desire and energy of the «learning community» (teachers, school administration, parents, students), and is based on certain key assumptions. Special attention is drawn to basic assumptions comparison of both above approaches generally built on different intellectual, methodological and theoretical principles which caused the initial lack of interaction between them. The merger of two approaches at the end of the twentieth century is considered as a fact of overcoming isolation of both directions that led to their mutual enrichment and more active and fruitful influence on educational policy. It is summarized in the article that the best achievements of the educational change theory give modern scientists the opportunity to apply consistent actions and provide evaluation of recent reforms in secondary education, as well as to foresee the future development of the school.